An optimal general type-2 fuzzy controller for Urban Traffic Network. (January 2017) - Khooban, Mohammad Hassan; Vafamand, Navid; Liaghat, Alireza; Dragicevic, Tomislav
Abstract: Urban traffic network model is illustrated by state-charts and object-diagram. However, they have limitations to show the behavioral perspective of the Traffic Information flow. Consequently, a state space model is used to calculate the half-value waiting time of vehicles. In this study, a combination of the general type-2 fuzzy logic sets and the Modified Backtracking Search Algorithm (MBSA) techniques are used in order to control the traffic signal scheduling and phase succession so as to guarantee a smooth flow of traffic with the least wait times and average queue length. The parameters of input and output membership functions are optimized simultaneously by the novel heuristic algorithm MBSA. A comparison is made between the achieved results with those of optimal and conventional type-1 fuzzy logic controllers. Highlights: A new optimal controller based on General Type-II Fuzzy Logic is presented. The proposed method guaranties stability and robustness. This novel technique is computationally simple and has not any complexity. The proposed controller can be used in different configurations of Urban Traffic Systems.